2017
DOI: 10.1093/ejcts/ezx279
|View full text |Cite
|
Sign up to set email alerts
|

Management of tricuspid valve regurgitation

Abstract: Tricuspid regurgitation (TR) is a very frequent manifestation of valvular heart disease. It may be due to the primary involvement of the valve or secondary to pulmonary hypertension or to the left-sided heart valve disease (most commonly rheumatic and involving the mitral valve). The pathophysiology of secondary TR is complex and is intrinsically connected to the anatomy and function of the right ventricle. A systematic multimodality approach to diagnosis and assessment (based not only on the severity of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(39 citation statements)
references
References 67 publications
0
35
0
4
Order By: Relevance
“…Interest in the tricuspid valve has increased in recent years (13)(14)(15) with the recognition of the impact of secondary tricuspid regurgitation on outcomes (1,2,5,7,16,17) and the benefits of tricuspid repair (6,18). TR is an independent predictor of long-term mortality (2,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in the tricuspid valve has increased in recent years (13)(14)(15) with the recognition of the impact of secondary tricuspid regurgitation on outcomes (1,2,5,7,16,17) and the benefits of tricuspid repair (6,18). TR is an independent predictor of long-term mortality (2,7).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of secondary TR with mitral valve disease is >30% (13,14), with some studies suggesting that more than 1.6 million patients in the United States may have this disease (19).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of the RV with TR is complex. Treatment options are governed by the underlying aetiology (Table 2) and hence an understanding of the mechanisms for TR is essential (53) (Fig. 4).…”
Section: Aetiology: Modern Day Causes Of Tricuspid Regurgitation and mentioning
confidence: 99%
“…Both late residual TR seen post mitral valve surgery (3) and isolated severe TR (4) have excess mortality and morbidity. Management guidelines remain ill defined since prospective outcome data are limited (5). Further, surgical TV intervention studies have suggested variable outcomes and this conflicting data have led to confusion as to optimal management in this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…24 The TV apparatus can be divided into several components: the fibrous annulus, anterior leaflet (AL), septal leaflet (SL) and posterior/inferior leaflet (PL/IL), anterior and posterior papillary muscles, and the chordal attachments. 21,[25][26][27][28][29] The annular plane of the TV is nearly vertical and approximately 45° from the sagittal plane. The 3 TV leaflets vary in circumferential and radial size; the AL being the longest radial leaflet with the largest area and greatest motion.…”
Section: A Look At the Anatomy Of The Tri Cus Pid Valvementioning
confidence: 99%